2001
DOI: 10.1046/j.1365-2702.2001.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards the eradication of head lice: literature review and research agenda

Abstract: Head lice infestation is a public health issue. In the effort to compile an evidence-base about the physiology, detection, treatment, effects and management strategies of head lice infestations we reviewed current literature. This literature signalled significant evidence gaps and these gaps provide incentives for further research. Our conclusions from the literature are that parents of children are responsible for head lice detection and treatment but have varying access to advice about how best to treat this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
1
15
1
3
Order By: Relevance
“…Previous reports showed that the increase in the size of family is the main factor facilitating the transmission of HLI [6,10]. It has been proposed that larger families may pay less attention to their children due to lack of support and financial limitations [11]. Contrary to common belief, our results indicate that large family decreases the risk of HLI.…”
contrasting
confidence: 98%
“…Previous reports showed that the increase in the size of family is the main factor facilitating the transmission of HLI [6,10]. It has been proposed that larger families may pay less attention to their children due to lack of support and financial limitations [11]. Contrary to common belief, our results indicate that large family decreases the risk of HLI.…”
contrasting
confidence: 98%
“…Son yıllarda görülme sıklığı Kuzey ve Güney Amerika'da, Avrupa'da, Asya'da, Avustralya'da ve Türkiye'de artma eğilimindedir (3). PK morbiditesiyle ilgili sağlık kayıtlarının sınırlı sayıdaki ülkede mevcut olduğu, onların da süreklilik göstermediği (5,6), sorunun kişiler tarafından zor ifade edildiği ya da çok az konuşulduğu, hatta pek çok kişinin enfekte olduğu fikrini reddedebildiği ya da bunu tehdit olarak görmeyebildiği ve konakçının fiziksel etkilerini geç fark edebildiği düşünülürse, PK'nin artan görülme sıklığı, buzdağının sadece görünen kısmıdır (6,7). PK'nin görülme sıklığı yüksek olmasına, bir bireyden diğerine kolaylıkla geçebilmesine ve aynı anda çok sayıda kişiyi etkilemesine karşın, bugün diğer sağlık sorunları içinde düşük öncelikli bir konudur.…”
Section: Introductionunclassified
“…Dies verursacht bei allen Beteiligten erheblichen Stress [2,3] . Obwohl ü blicherweise nur als " L ä stling " betrachtet, verursacht Pediculus capitis dem Gesundheitswesen erhebliche Kosten, f ü hrt zu Unterrichtsausfall und -besonders bei allein erziehenden M ü ttern / V ä tern -zu Konfl ikten in der Berufsaus ü bung [4] . Bislang wenig Bedeutung geschenkt wurde den psychosozialen Folgen von Kopfl ausbefall.…”
Section: Einf ü Hrungunclassified